TECHNICAL APPROACH TO THE SEQUENCE OF TEACHING AND USE OF HISTOLOGICAL TERMINOLOGY OF STRUCTURE OF BULBUS OCULI IN THE PROCESS OF STUDIES OF MEDICAL FACULTY STUDENTS - Vaduk, R.L. (World of Medicine and Biology, 2013)
The article is sanctified to the questions of sequence of teaching of structure of eye and relared structures in a course the studies of students of medical faculty within the limits of the credit-module system with an accent on correct application of new list of histological terminologia.
Keywords: histology; ophthalmology; successive of teaching; terms